Revisão taxonômica do grupo limata de Crematogaster Lund, 1831 (Formicidae: Myrmicinae: Crematogastrini) - FELIZARDO, Sherlem Patricia de Seixas (Universidade Federal do Pará, 2013)
The large number of species, peculiar morphology and its wide geographic distribution make the genus Crematogaster one of the most complex taxonomically among ants. About 780 species and subspecies were described and constants changes are made over time due to its morphological variety. A few revisions only for regional fauna were made for this genus. This study is a taxonomic revision of the species group Crematogaster limata. Six species are redescribed: Crematogaster brasiliensis Mayr, 1878, C. carinata Mayr, 1862, C. levior Longino, 2003, C. Limata Smith, 1858, C. longispina Emery, 1890, C. tenuicula Forel, 1904 and four new species are described: Crematogaster n. sp. 1, Crematogaster n. sp. 2, Crematogaster n. sp. 3, Crematogaster n. sp. 4. The taxa Crematogaster longispina var. boliviana was raised to species level and redescribed. Maps of the geographical distribution for it species and a key for species based in workers are presented.